Integration of Population and Environmental Education in Strengthening Social Advocacy among Urban Communities : A Study of Migrant Women within the Landscape of Urban Prostitution - Syaifudin, Syaifudin; Purwanto, Agung; Budiaman, Budiaman (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the relationship between urbanization, urban ecological pressure, and the marginalization of migrant women within the landscape of covert prostitution in the SPA industry in DKI Jakarta, while also examining the role of Population and Environmental Education (PKLH) (Pendidikan Kependudukan dan Lingkungan Hidup) as a pedagogy of social advocacy for strengthening the rights and empowerment of urban migrant women. The study employed a qualitative, critical case-study approach. Data were collected through in-depth interviews with migrant women working in SPA establishments, activists from non-governmental organizations, academics, and local government officials, supported by observation and documentary study. The data were analyzed interactively through data reduction, thematic categorization, critical interpretation, and source triangulation. The findings indicate that urbanization in DKI Jakarta not only generates economic growth but also reproduces social inequality and ecological vulnerability, thereby intensifying the marginalization of migrant women. Ecological pressures in the form of flooding, pollution, poor sanitation, and limited access to healthy living spaces intersect with low educational attainment, weak social protection, and restricted access to formal employment, pushing migrant women into exploitative informal work sectors. This study concludes that PKLH needs to be reconstructed as a critical, participatory, and emancipatory pedagogy of social advocacy to strengthen rights awareness, economic empowerment, and socio-ecological justice for urban migrant women.